Pharmacological inactivation of the PI3K p110δ prevents breast tumour progression by targeting cancer cells and macrophages - Goulielmaki, Evangelia (Cell Death Dis, 2018)
Patient selection for PI3K-targeted solid cancer treatment was based on the PIK3CA/PTEN mutational status. However, it is increasingly clear that this is not a good predictor of the response of breast cancer cells to the anti-proliferative effect of PI3K inhibitors, indicating that isoform(s) other than p110α may modulate cancer cells sensitivity to PI3K inhibition. Surprisingly, we found that although no mutations in the p110δ subunit have been detected thus far in breast cancer, the expression of p110δ becomes gradually elevated during human breast cancer progression from grade I to grade III. Moreover, pharmacological inactivation of p110δ in mice abrogated the formation of tumours and the recruitment of macrophages to tumour sites and strongly affected the survival, proliferation and apoptosis of grafted tumour cells. Pharmacological inactivation of p110δ in mice with defective macrophages or in mice with normal macrophages but grafted with p110δ-lacking tumours suppressed only partly tumour growth, indicating a requisite role of p110δ in both macrophages and cancer cells in tumour progression. Adoptive transfer of δ(D910A/D910A) macrophages into mice with defected macrophages suppressed tumour growth, eliminated the recruitment of macrophages to tumour sites and prevented metastasis compared with mice that received WT macrophages further establishing that inactivation of p110δ in macrophage prevents tumour progression. Our work provides the first in vivo evidence for a critical role of p110δ in cancer cells and macrophages during solid tumour growth and may pave the way for the use of p110δ inhibitors in breast cancer treatment.